Holocene thermokarst dynamics in Central Yakutia – A multi-core and robust grain-size endmember modeling approach. (15th August 2019) - Ulrich, Mathias; Matthes, Heidrun; Schmidt, Johannes; Fedorov, Alexander N.; Schirrmeister, Lutz; Siegert, Christine; Schneider, Birgit; Strauss, Jens; Zielhofer, Christoph
Abstract: Differentiating thermokarst basin sediments with respect to the involved processes and environmental conditions is an important tool to understand permafrost landscape dynamics and scenarios and future trajectories in a warming Arctic and Subarctic. Thermokarst basin deposits have complex sedimentary structures due to the variability of Yedoma source sediments, reworking during the Late Glacial to Holocene climate changes, and different stages of thermokarst history. Here we reconstruct the dynamic growth of thermokarst lakes and basins and related changes of depositional conditions preserved in sediment sequences using a combination of biogeochemical data and robust grain-size endmember analysis (rEMMA). This multi-proxy approach is used on 10 sediment cores (each 300–400 cm deep) from two key thermokarst sites to distinguish four time slices that describe the Holocene thermokarst (lake) basin evolution in Central Yakutia (CY). Biogeochemical proxies and rEMMA reveal fine-grained sedimentation with rather high lake levels and/or reducing conditions, and coarse-grained sedimentation with rather shallow lake levels and/or oxidizing (i.e. terrestrial) conditions in relation to distal and proximal depositional and post-sedimentary conditions. Statistical analysis suggests that the biogeochemical parameters are almost independent of thermokarst deposit sedimentology. Thus, the biogeochemical parameters are considered as signals of secondary (post-sedimentary) reworking. The rEMMA results are clearly reflecting grain-size variations and depositional conditions. This indicates small-scale varying depositional environments, frequently changing lake levels, and predominantly lateral expansion at the edges of rapidly growing small thermokarst lakes and basins. These small bodies finally coalesced, forming the large thermokarst basins we see today in CY. Considering previous paleoenvironmental reconstructions in Siberia, we show the initiation of thaw and subsidence during the Late Glacial to Holocene transition between about 11 and 9 cal kyrs BP, intensive and extensive thermokarst activity for the Holocene Thermal Maximum (HTM) at about 7 to 5 cal kyrs BP, severely fluctuating water levels and further lateral basin growth between 3.5 cal kyrs BP and 1.5 cal kyrs BP, and the cessation of thermokarst activity and extensive frost-induced processes (i.e. permafrost aggradation) after about 1.5 cal kyrs BP. However, gradual permafrost warming over recent decades, in addition to human impacts, has led to renewed high rates of subsidence and abrupt, rapid CY thermokarst processes. Highlights: Small thermokarst lakes and basins grew rapidly during the Holocene Thermal Maximum. Short-term phases of forcing climate lead to very active thermokarst processes. Endmember analysis reveals different depositional environments in growing lakes. Distal and proximal depositional and post-sedimentary conditions are differentiated. Sedimentological and biogeochemical characteristics are weakly correlated.